Complex analysis - Gherardelli,F (CIME Summer Schools, 2011)
A. Andreotti: Nine lectures on complex analysis.- J.J. Kohn: Propagations of singularities for the Cauchy-Riemann equations.- Yum-Tong Siu: The mixed case of the direct image theorem and its applications.